a) 6/2: (5/2 - 4/2) * (2/1 + 2) =?
b) (3/2 * 11 +1/11): 5/2*(4 - 18 +1/7) =?
c) [(5*2)/3 -5*2/3] : (5*2)=?
proszę szybko mam to na poniedziałek z góry dziękuję:)​


Odpowiedź :

Odpowiedź:

a) 24

b) -5044/55

c) 0

Szczegółowe wyjaśnienie:

a) 6/2 : (5/2 - 4/2) * (2/1 + 2) = 3 : (1/2) * 4 = 3*2*4 = 24

b) (3/2 * 11 + 1/11) : 5/2*(4 - 18 + 1/7) = (33/2 + 1/11) : 5/2*(-13 6/7) =

(363/22 + 2/22) * 2/5 * (-97/7) = 364/22 * 2/5 * (-97/7) = -(52*1*97)/(11*5) =

-5044/55

c) [(5*2)/3 -5*2/3] : (5*2) = (10/3 - 10/3) : 5/2 = 0 * 2/5= 0